Neuropeptide S Ameliorates Cognitive Impairment of APP/PS1 Transgenic Mice by Promoting Synaptic Plasticity and Reducing Aβ Deposition - Zhao, Peng; Qian, Xiaohang; Nie, Yunjuan; Sun, Na; Wang, Zhongxuan; Wu, Jiajun; Wei, Chen; Ma, Ruikun; Wang, Zhe; Chai, Gaoshang; Li, Yuqing (Frontiers in Behavioral Neuroscience, 2019)
Alzheimer's disease (AD) is a devastating disease in the elderly with no known effective treatment. It is characterized by progressive deterioration of memory and cognition. Many new potential targets are being investigated to develop effective therapeutic strategies for AD. Neuropeptide S (NPS) is an endogenous peptide in the central nervous system, which has been shown to play a beneficial role in learning and memory. However, whether NPS can ameliorate cognitive deficits in AD remains unclear. In this study, we examined the effects of NPS treatment on the cognitive behaviors and pathological hallmarks in 8-month-old APPswe/PS1dE9 (APP/PS1) AD mice. We found that the APP/PS1 mice exhibited lower levels of NPS receptors (NPSR) in the hippocampal area, and NPS administration increased c-Fos expression in the hippocampus and cortex, which suggests the NPS/NPSR system may contribute to the pathogenesis of AD. After an intracerebroventricular injection of NPS (1 nmol) for two weeks, we found NPS treatment ameliorated spatial memory deficits and promoted dendrite ramification and spine generation in hippocampal CA1 neurons, which was accompanied by the upregulation of postsynaptic density protein 95 and synapsin1. We also demonstrated that the injection of NPS decreased Aβ plaque deposits by decreasing the γ-secretase activity and the phosphorylation of APP at Thr668. Furthermore, application of NPS reversed the deficits in hippocampal late-phase long-term potentiation. These findings suggest NPS attenuated cognitive deficits by reducing pathological features in APP/PS1 mice, and NPS might be a potential therapeutic agent for AD.